DESIGN, SIMULATION AND OPTIMIZATION OF NACA 0021 AEROFOIL BLADE USING ANSYS FLUENT - Yunusa, Hamza Abba; Tokan, A.; Fachway, A. A. (FUDMA Journal of Sciences, 2025)
Vertical Axis Wind Turbines (VAWTs) often exhibit reduced aerodynamic efficiency due to high drag forces, flow separation, and poor lift characteristics under low or turbulent wind conditions. The widely used NACA 0021 aerofoil remains structurally robust but suffers limitations at high angles of attack and low Reynolds numbers, conditions typical of VAWT operation. This study applies Computational Fluid Dynamics (CFD) using ANSYS Fluent to redesign and optimize the NACA 0021 profile for improved aerodynamic performance. Simulations were conducted at wind speeds of 5–20 m/s and angles of attack (AOA) from 0°–360° using the k–ω SST turbulence model. The optimized profile achieved a maximum lift coefficient of 1.5 and a lift-to-drag ratio of 88.1 at 20 m/s and 180° AOA, while a minimum drag coefficient of 0.012 occurred at 90° AOA and 15 m/s. These values notably exceed standard NACA 0021 benchmarks; however, some extreme values may be influenced by numerical effects and warrant experimental validation. Overall, the optimized geometry demonstrates potential for improving VAWT efficiency, especially in variable-wind environments.
Keywords: Aerofoil blade; Design and Simulation; Optimization; ANYSYS Fluent